2021
DOI: 10.3390/educsci11080440
|View full text |Cite
|
Sign up to set email alerts
|

High-School Students’ Topic-Specific Epistemic Beliefs about Climate Change: An Assessment-Related Study

Abstract: This study belongs to assessment-related research and aimed to investigate Finnish high-school students’ (n = 211) topic-specific epistemic beliefs about climate change and whether the Norwegian topic-specific epistemic beliefs questionnaire (TSEBQ) was also valid among Finnish respondents. Thus, research data were not only derived from the TSEBQ but also from topic knowledge tests and students’ views on their favorite school subjects and interest in science subjects. Principal component analysis (PCA) showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Ratinen and Uusiautti [65] found that mitigation knowledge of CC among Finnish female upper secondary students was better than among Finnish male upper secondary students. Yli-Panula, Laakkonen, and Vauras [66] showed with Finnish upper secondary students that the ability to learn about and solve CC issues is linked not only to topic knowledge but also to people's beliefs regarding the topic, a result congruent with those generated by Leiserowitz [67] and Poortinga et al [68]. The research by Yli-Panula et al [66] also revealed that upper secondary school students' academic achievements are influenced by the structure and certainty of knowledge, as well as by the justification of knowing studied in relation to CC, which are results that are in line with those of Cano [69] and Mason et al [70].…”
Section: Challenges Of Climate Change Education (Cce)mentioning
confidence: 98%
“…Ratinen and Uusiautti [65] found that mitigation knowledge of CC among Finnish female upper secondary students was better than among Finnish male upper secondary students. Yli-Panula, Laakkonen, and Vauras [66] showed with Finnish upper secondary students that the ability to learn about and solve CC issues is linked not only to topic knowledge but also to people's beliefs regarding the topic, a result congruent with those generated by Leiserowitz [67] and Poortinga et al [68]. The research by Yli-Panula et al [66] also revealed that upper secondary school students' academic achievements are influenced by the structure and certainty of knowledge, as well as by the justification of knowing studied in relation to CC, which are results that are in line with those of Cano [69] and Mason et al [70].…”
Section: Challenges Of Climate Change Education (Cce)mentioning
confidence: 98%